BIM Capabilities towards Better Safety Climate in the Malaysian Construction Industry. Issue 1 (1st October 2022) - Adillah Ismail, Noor Akmal; Basirah Baharun, Bibi Nur; Adnan, Hamimah; Maisham, Mysarah; Asyikin Mahat, Noor Aisyah
Abstract: The Malaysian construction industry are dealing with numerous cases of permanent injuries and death of workers in construction sites. This has caused lack of productivity and also losses of human resources. The urging working condition aiming for on time completion has led to unsafe working behaviour due to the top management pressure. This is where Building Information Modelling (BIM) came into view to increase the safety on site environment and through design phase by using technology to overcome human inconsistency behaviour. However, the lack of BIM implementation in Malaysia also causes even lesser implementation of BIM in safety of construction. Therefore, this study aims to investigate the BIM capabilities towards better safety climate in the Malaysian construction industry. A qualitative approach was used through semi-structured interviews and discussion with selected representatives from both private and government sectors. All the interviewed data were then analysed using content analysis technique which correlated the findings with the literature review to support the findings. Based on the findings, it can be concluded that (1) Visualisation for Safety, and (2) Simulation for Safety are the most potential BIM capabilities to be implemented in the construction industry for improving safety climate by using BIM technology. Significantly, the study provides insights towards outlining potential BIM capabilities on policy or Safety Rules and Procedure implementation by the government authority or organizations' top management.